The Effect Of Potato Starch Substitution On The Quality Of Pukis Cake - Gustina, Vika Afnelisa; Gusnita, Wiwik (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
This study aims to analyze the quality of the pukis cake with potato flour substitution as much as 20%, 40% and 60% which includes volume, shape, color, aroma, texture and taste. This research was conducted at the culinary arts workshop majoring in family welfare science in January 2022. This type of research was a pure experiment using the Completely Randomized Design (CRD) method which had 3 treatments and 3 repetitions. The object of this research is the pukis cake with potato flour substitution as much as 20%, 40% and 60% of the quality of the pukis cake. The types and sources of data used are primary data obtained directly from 5 expert panelists by filling out the organoleptic test format for the quality of the pukis cake. Data analysis used Analysis of Variance (ANOVA). If the analysis of variance shows Fcount > Ftable, Duncan's test will be carried out. The results showed that the substitution of potato flour had no significant effect on the quality of shape, color, aroma and taste. Meanwhile, a significant effect was found on the quality of the swelled volume, soft texture and porous texture of the pukis cake. The results of the quality test of pukis cake with potato flour substitution were the best in the X1 treatment with 20% potato starch substitution.